2012
DOI: 10.1371/journal.pone.0041311
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Collicular Interaction: Modulation of Auditory Signal Processing in Amplitude Domain

Abstract: In the ascending auditory pathway, the inferior colliculus (IC) receives and integrates excitatory and inhibitory inputs from many lower auditory nuclei, intrinsic projections within the IC, contralateral IC through the commissure of the IC and from the auditory cortex. All these connections make the IC a major center for subcortical temporal and spectral integration of auditory information. In this study, we examine bilateral collicular interaction in modulating amplitude-domain signal processing using electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…Electric stimulus intensity was regulated within 20–50 μA, as required. The output of the electronic stimulator was connected to a stimulation isolator (ISO-Flex, A.M.P.I, Israel), and the output of the stimulus isolator was connected to a pair of custom-made tungsten wire electrodes (FHC Inc., Bowdoin, ME, USA) (tip: <10 μm; intertip distance: ≤100 μm) [ 32 ] for stimulating and activating the AC of the bat. The gap between the electric ending and the acoustic stimulus onset was fixed at 5–10 ms, and the paired stimulus was delivered to the bat at 2 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…Electric stimulus intensity was regulated within 20–50 μA, as required. The output of the electronic stimulator was connected to a stimulation isolator (ISO-Flex, A.M.P.I, Israel), and the output of the stimulus isolator was connected to a pair of custom-made tungsten wire electrodes (FHC Inc., Bowdoin, ME, USA) (tip: <10 μm; intertip distance: ≤100 μm) [ 32 ] for stimulating and activating the AC of the bat. The gap between the electric ending and the acoustic stimulus onset was fixed at 5–10 ms, and the paired stimulus was delivered to the bat at 2 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…The degree of bilateral collicular interaction was dependent upon the BF difference between the electrically stimulated IC neurons and the modulated IC neurons. The percent modulation in the number of impulses was larger for the neuron with a smaller BF difference than for the neuron with a larger BF difference (Mei et al, 2012b). …”
Section: Bilateral Collicular Interaction In Auditory Signal Processingmentioning
confidence: 99%
“…The excitatory modulation of bilateral collicular interactions expands the RIFs and FTCs of facilitated IC neurons but decreased the slope of their RIFs and Q 10 value of their FTCs for wider amplitude and frequency responses to sound stimuli. Conversely, the inhibitory modulation of bilateral collicular interaction sharpens the RIFs and FTCs of inhibited IC neurons but increased the slope of their RIFs and Q 10 value of their FTCs for sharper sensitivity to sound amplitude and frequency (Mei et al, 2012b; Cheng et al, 2013). It is also suggested that the small proportion of bilateral collicular excitatory interactions between neurons in corresponding frequency laminae and the large proportion of bilateral collicular inhibitory interactions between neurons in different frequency laminae may be involved in the formation of binaural neurons (i.e., excitation–excitation, EE neurons that can be excited by same BF sound stimulation to either ear; excitation–inhibition, EI neurons that are strongly excited by sound stimulation to the contralateral ear and are inhibited by sound stimulation to the ipsilateral ear; Mei et al, 2012a).…”
Section: Bilateral Collicular Interaction In Auditory Signal Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…One IC also receives inputs from the opposite IC; the commissural of IC (CoIC), which interconnects two ICs, mediates the intercollicular effects on sound information processing [ 15 18 ]. Our recent studies show that real-time focal electrical stimulation of one IC produces widespread inhibition and focused facilitation of the opposite IC in the amplitude domain [ 19 21 ]. In this study, we further explore the role of intercollicular effects via CoIC on the functional plasticity of the amplitude domain of IC neurons by auditory conditioning that acoustic stimulation paired by 30 min of IC focal electrical stimulation.…”
Section: Introductionmentioning
confidence: 99%